2022
DOI: 10.1128/msphere.00239-22
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Menstruation, Community Type, and an Oral Yeast Probiotic on the Vaginal Microbiome

Abstract: How to define and promote a healthy state of the vaginal microbiome is not well understood. Knowledge of which underlying factors shape the microbial community composition of the vagina and how to modulate them will contribute to vaginal disease prevention and improve fertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 51 publications
(81 reference statements)
2
5
0
Order By: Relevance
“…Importantly, we did not observe significant antagonistic activity between S. cerevisiae CNCM I-3856 and the tested lactobacilli regarding C. albicans inhibition, highlighting that they can be applied together without loss of activity. Furthermore, it is plausible that S. cerevisiae CNCM I-3856 will not have major antagonistic effects with the lactobacilli comprising the natural vaginal microbiome, as we have shown for the vaginal lactobacilli in this paper, and recently demonstrated in healthy women 14 . This is also relevant for oral S. cerevisiae CNCM I-3856 administration, as it has previously been demonstrated that after its oral administration in women S. cerevisiae CNCM I-3856 can be recovered from vaginal samples of at least 18% to 21% of participants, depending on the analysis 14 , 27 .…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Importantly, we did not observe significant antagonistic activity between S. cerevisiae CNCM I-3856 and the tested lactobacilli regarding C. albicans inhibition, highlighting that they can be applied together without loss of activity. Furthermore, it is plausible that S. cerevisiae CNCM I-3856 will not have major antagonistic effects with the lactobacilli comprising the natural vaginal microbiome, as we have shown for the vaginal lactobacilli in this paper, and recently demonstrated in healthy women 14 . This is also relevant for oral S. cerevisiae CNCM I-3856 administration, as it has previously been demonstrated that after its oral administration in women S. cerevisiae CNCM I-3856 can be recovered from vaginal samples of at least 18% to 21% of participants, depending on the analysis 14 , 27 .…”
Section: Discussionsupporting
confidence: 54%
“…Several studies show that oral (as a food supplement) and vaginal (generally as a drug, with a more complex regulatory route) intake of different probiotic species and strains is associated with improved clinical signs 11 – 13 . In addition, no side effects have been observed or reported upon probiotic use in healthy women 14 or women suffering from VVC 11 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 96%
“…During menses, increased diversity (Krog et al, 2022) and decreased Lactobacillus abundances (Song et al, 2020) were observed. During the follicular and luteal phases, the abundance of Lactobacillus is expanded, and the vaginal microbiome of more women becomes dominated by Lactobacillus due to the increase of estradiol (Gajer et al, 2012;Song et al, 2020;Jie et al, 2021;Krog et al, 2022;Oerlemans et al, 2022). In postmenopausal women, species richness was decreased, but species diversity was significantly increased (Kim et al, 2021).…”
Section: Normal Cervicovaginal Microbiomementioning
confidence: 99%
“…4 On the other hand, L. iners seems to resist and dominate the vaginal environment when in the presence of microbiota disturbances such as menstruation. 23,24 However, it should be considered that CSTIII has been associated with several sexually transmitted infections 25,26 because infections caused by C. trachomatis and by human papillomavirus (HPV) are reinforcing the concerns about the protective role of L. iners in vaginal microbiota. The findings of the current study show that women with CSTIII who include milk and/or dairy products in their diet have increased L. crispatus RAs.…”
Section: Discussionmentioning
confidence: 99%
“…The CSTIII has been associated with a higher temporal instability because it can alternate to CSTIV and vice-versa in a short period 4 . On the other hand, L. iners seems to resist and dominate the vaginal environment when in the presence of microbiota disturbances such as menstruation 23,24 . However, it should be considered that CSTIII has been associated with several sexually transmitted infections 25,26 because infections caused by C. trachomatis and by human papillomavirus (HPV) are reinforcing the concerns about the protective role of L. iners in vaginal microbiota.…”
Section: Discussionmentioning
confidence: 99%